Harnessing Artificial Intelligence (AI) in Personalizing Learning at Palembang Vocational Schools: An Exploratory Study - Dahnial Dahnial; Ilsa Palingga Ninditama; Dita Rahmawati; M Bambang Purwanto (Lembaga Pengembangan Kinerja Dosen, 2025)
This study investigates the application of artificial intelligence (AI) to enhance personalized learning in Vocational High Schools (SMKs) in Palembang City. The background of this research is based on the need for adaptive learning to accommodate the diverse characteristics of vocational students, as well as the challenges faced by conventional learning methods. This study employs a descriptive, qualitative approach with an exploratory design. Data was collected through in-depth interviews and observations of teachers and students in five vocational schools, both public and private. The results show that AI has been utilized as a Learning Management System (LMS), an Android-based application, and an automated evaluation system, allowing teachers to monitor individual student progress. The main obstacles faced include a limited understanding of technology among teachers, uneven network infrastructure, and concerns about teachers being displaced by automated systems. On the other hand, AI also opens up opportunities to enhance learning motivation, improve teaching efficiency, and provide a more adaptive learning experience. This research contributes to the understanding of AI's application in vocational schools and lays the foundation for developing a more inclusive and responsive digital education policy.